Philanthropy, political connection and debt finance: Reciprocal behavior of governments and private enterprises. Issue 4 (7th November 2016) - Li, Weian; Wang, Pengcheng
Abstract : Purpose: Philanthropy is taken as a strategic behavior by private enterprises to obtain financial resources from governments. This paper aims to examine the relationship between private enterprise philanthropy and the debt finance, further investigating the way by which governments exchange resources with private enterprises. Design/methodology/approach: The paper opted for an empirical study using a sample of 1, 489 Chinese private-listed companies from 2007 to 2010. The study analyzed the relationship between philanthropy and debt finance based on the resource dependence theory and social exchange theory and tested the moderating effect of political connection. Findings: Philanthropy can help private enterprises to get the debt finance, and this effect occurs mainly among the political connected private enterprises; the higher degree of credit allocation marketization is, the less philanthropy can affect the debt finance and the less influence political connection can exert on that relationship. Philanthropy contributes to debt financing mainly because it can help obtain more long-term loan, and this effect is more obvious for politically connected private enterprises in regulated industries. Originality/value: This paper verifies the action logic of private enterprises philanthropy from the perspective of exchange behavior, which is helpful to understand the motive and influence of private enterprises philanthropy.